Successful intravenous thrombolysis for ischemic stroke as a complication of coronary intervention in patients with ticagrelor pretreatment. (January 2020) - Wright, Sarah L.; Jahangiri, Bijan; Smyth, David W.; Fink, John N.; Ho, Roger; Choi, Philip M.C.; Wu, Teddy Y.
Highlights: It is uncertain if ticagrelor pre-treatment contraindicates stroke thrombolysis. More ischemic stroke patients eligible for thrombolysis would be on ticagrelor. Two stroke with ticagrelor pre-treatment and I.V. thrombolysis are reported. I.V. thrombolysis in this setting should be considered on case by case basis. Abstract: Ticagrelor is an antiplatelet agent used for treatment of coronary artery disease via inhibition of the P2Y12 receptor. Based on limited literature the safety of intravenous thrombolysis for ischemic stroke in patients with ticagrelor pretreatment is unknown. We present two patients established on ticagrelor treated with intravenous thrombolysis for acute ischemic stroke complicating coronary intervention.